Taxonomy and bioacoustics of little-known Grylloidea crickets (Orthoptera, Ensifera) from Mindanao, Philippines - Tan, Ming Kai; Salvador, Jewel Anne G.; Sabang, Aira Mae M.; Bahoy, Daphne Cayle M.; Nuñeza, Olga Macas; Robillard, Tony (Zootaxa, 2023)
Orthopteran surveys were conducted recently on Mindanao Island of the Philippines. Four species new to science are described here: Mistshenkoana lunotan sp. nov., Mistshenkoana higaonon sp. nov. and Ectatoderus dubius sp. nov. from Misamis Oriental; and Phaloria (Phaloria) rotundata sp. nov. from Agusan del Sur. Based on new collected material, Madasumma fuscoirrorata Chopard, 1925, first described based on a single female from Mindanao, is transferred to Varitrella (Cantotrella) fuscoirrorata (Chopard, 1925) comb. nov. We also describe the male of this species for the first time. Madasumma zamboanga Otte, 2007, first described from Zamboanga del Norte (Mindanao), is also transferred to Mnesibulus (Amnesibulus) and redescribed: Mnesibulus (Amnesibulus) zamboanga (Otte, 2007) comb. nov. We also describe previously unknown calling songs of seven species: Falcerminthus parvus (Baroga-Barbecho & Robillard, 2020), Ajorama balatukanis Otte, 1988, Varitrella (Cantotrella) bakeri (Chopard, 1925), Varitrella (Cantotrella) fuscoirrorata (Chopard, 1925) comb. nov., Phaloria (Phaloria) rotundata sp. nov., Ornebius bioculatus Tan et al., 2019 and Ectatoderus dubius sp. nov.